2019
DOI: 10.1002/jcb.29160
|View full text |Cite
|
Sign up to set email alerts
|

miR‐522 stimulates TGF‐β/Smad signaling pathway and promotes osteosarcoma tumorigenesis by targeting PPM1A

Abstract: Osteosarcoma (OS) is identified as an aggressive malignancy of the skeletal system and normally occurs among young people. It is well accepted that microRNAs are implicated in biological activities of diverse tumors. Although miR‐522 has been proved to elicit oncogenic properties in a wide range of human cancers, the physiological function and latent mechanism of miR‐522 in OS tumorigenesis remain largely to be probed. In the current study, we certified that miR‐522 was highly expressed in OS cells and present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 33 publications
(60 reference statements)
0
9
0
Order By: Relevance
“…Furthermore, accumulating evidence has demonstrated that the TGFβ/SMAD pathway is involved in OS progression. For instance, miR-522 promotes osteosarcoma tumorigenesis by targeting PPM1A via the TGF-β/SMAD signaling pathway (Xu and Liu, 2019). In addition, GDF15 promotes osteosarcoma cell migration and invasion by regulating the TGF-β signaling pathway .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, accumulating evidence has demonstrated that the TGFβ/SMAD pathway is involved in OS progression. For instance, miR-522 promotes osteosarcoma tumorigenesis by targeting PPM1A via the TGF-β/SMAD signaling pathway (Xu and Liu, 2019). In addition, GDF15 promotes osteosarcoma cell migration and invasion by regulating the TGF-β signaling pathway .…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence has illustrated that numerous miRNAs are dysregulated in osteosarcoma and serve as an oncogene or tumor suppressor ( 13 , 26 ). Here, miR-487a was significantly upregulated in osteosarcoma cells and tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Several experimentally validated targets of miR-522 in human cancers have been documented, including ABCB5, BLM, MAOB, PHLPP1, DKK1, SFRP2, DENND2D, SOCS5 and PPM1A [20,[23][24][25][26][29][30][31]45]. PTGR1 and SOCS3 are reported to be regulated by miR-522 to participate into the inflammation processes [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Several experimentally validated targets of miR-522 in human cancers have been documented, including ABCB5, BLM, MAOB, PHLPP1, DKK1, SFRP2, DENND2D, SOCS5 and PPM1A [20,[23][24][25][26][29][30][31]45].…”
Section: Discussionmentioning
confidence: 99%